Analisis Hukum dengan Ekonomi - Rusli, Hardijan (LAW REVIEW, 2005)
Is the task of law aimed at increase of economic efficiency? The answer to this depends on the political tendency of the reader. For reader who are for market and economic liberal will certainly answer yes, while others who do not agree with this idea, especially those who are "leftists" (disagree with market and economic liberalization), will positively oppose such opinion by saying that the main task of law is to create justice, support right and redistribution. It has to be acknowledged that the answer given by the supporter Â of economic idea of law is deemed weak and vague compared to that given by the leftists. Indeed, the proponents of the idea that law is supposed to achieve economic development realize that the main purpose of law is to serve justice and support right, although in some respects advocate the idea that law should also aim at economic liberalization. Many say that the origin of the legal approach to economy emerged in the Â USA in 1960s with the writings of Ronald Coase, Gido Catabresi and Richard Possnei: Like any other theories the School of Chicago traces hack its origin of inspiration from the combination of previous approaches.